The Effect of Spiritual Group Therapy on the Quality of Life and Empowerment of Women with Breast Cancer: A Randomized Clinical Trial in Iran - Momennasab, Marzieh (Journal of religion and health, 2024)
This randomized clinical trial was carried out on 74 women with breast cancer between May 2015 and April 2016 in the south of Iran. The patients were selected using a simple sampling method and randomly divided into an intervention (n = 30) and a control (n = 37) group. Five spiritual therapy sessions were conducted for the intervention group. Each session lasted one hour. The quality of life and empowerment of the patients were measured before and one month after the intervention. To collect data, four instruments were used, including a demographic information form, the European Organization for Research and Treatment of Cancer QOL questionnaire Cancer-30 (EORTC QLQ C-30), EORTC QLQ Breast-23 (EORTC QLQ-BR23), and the Cancer Empowerment Questionnaire (CEQ). After the intervention, a difference was observed between the groups concerning the mean score of general health (P = 0.016) and emotional function (P = 0.029), but there was no significant difference between the groups concerning the mean score of empowerment (P = 0.62). Thus, it appears that spiritual group therapy can improve the quality of life of this group of patients.IRCT registration number: IRCT 2014050417546N2.